The role of genre-based community music: A study of two UK ensembles. Issue 3 (1st December 2018) - Tapson, Kit; Daykin, Norma; Walters, David M.
Background: there is a growing trend towards addressing social inclusion through community music, and at the same time, increasing interest in the way that participatory music can benefit health and well-being. However, relatively little research has been undertaken on community ensembles that addresses personal and social well-being through genre-based music. This pilot study examined community music impacts and processes in contexts where there are higher than average health needs and well-being inequalities. Methods: participant observation and semi structured interviews were undertaken with music leaders, project managers and musicians in two UK ensembles: a Community Orchestra (CO) that focuses on reggae and a jazz Big Band (BB). Thematic analysis identified twelve key themes. Findings: while each ensemble addresses specific needs, common themes and challenges were identified. These include positive and negative experiences that are mediated by musical identity and genre, inclusive practices, the role of the Music Director (MD), community connections, and governance and structure. Conclusions: membership of a community ensemble can afford creative and educational opportunities as well as supporting the well-being of members and a wider sense of empowerment in the communities from which they are drawn.